Centrosomal aberrations in primary invasive breast cancer are associated with nodal status and hormone receptor expression - Schneeweiss, Andreas; Sinn, Peter; Ehemann, Volker; Khbeis, Tanja; Neben, Kai; Krause, Ulf; Ho, Anthony Dick; Bastert, Gunther; Krämer, Alwin (International journal of cancer, 2003)
Our purpose was to assess the presence of centrosomal aberrations as measured by immunohistochemistry in primary invasive breast cancer and their association with established and proposed prognostic factors. Tissue sections of 103 primary invasive breast cancers were examined using centrosome-specific antibodies to pericentrin and γ-tubulin. At least 3 different tumor regions per case were examined to determine maximum centrosomal aberration levels, which represent the proportion of cells with abnormal centrosomes in the region with the highest percentage of cells with centrosomal aberrations. The χ2 test was performed to evaluate the association of maximum centrosomal aberration levels with patient age; tumor size; nodal status; nuclear grade; hormone receptor and Her2/neu expression; proportion of Ki67-, p53- and Bcl-2-positive tumor cells; DNA index; S-phase fraction; and proliferation index. With pericentrin immunohistochemistry, maximum centrosomal aberration levels >35% were detectable in 92 of the 103 breast carcinomas (89%). We found a highly significant correlation of maximum centrosomal aberration levels above 35% with axillary nodal tumor involvement (p < 0.0001) and the absence of hormone receptors (p < 0.0001). In addition, there was a borderline significant relationship with age <50 years (p = 0.050) and Her2/neu overexpression (p = 0.050). Among node-negative patients, maximum centrosomal aberration levels >35% were also associated with an increased DNA index (p = 0.006). In a subset of patients, additional staining of centrosomes with a monoclonal anti-γ-tubulin antibody essentially confirmed these results. In primary invasive breast cancer, centrosomal aberrations are associated with those factors predicting a more aggressive course of disease. This might indicate a fundamental role of centrosomal dysfunction in disease evolution, possibly as a result of chromosome missegregation during mitosis. © 2003 Wiley-Liss, Inc.
Gesehen am 03.12.2021